2001
DOI: 10.1046/j.1570-7458.2001.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variability in diapause response of Japanese Orius species

Abstract: Interspecific and latitudinal variation in diapause characteristics were examined in 12 strains of Orius species (Heteroptera: Anthocoridae) including O. sauteri (Poppius), O. nagaii Yasunaga, O. minutus (L.), O. strigicollis (Poppius), and O. tantillus (Motschulsky) from Japan. A latitudinal cline was found in the photoperiodic response controlling reproductive diapause: the lower the latitude, the lower the diapause incidence and the shorter the critical daylength. To examine the overwintering success, eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 13 publications
2
41
0
Order By: Relevance
“…Murai et al (2001) reported that 28.6% of O. sauteri reared at 25°C using E. kuehniella eggs as the diet under long-day conditions (16L : 8D) did not lay eggs. Furthermore, Shimizu and Kawasaki (2001) reported the presence of non-ovipositing females even in the non-diapausing Okinawa strain of O. strigicollis reared as a colony at 20°C using E. kuehniella eggs as the diet under long-day conditions (16L : 8D). As shown in these results, nonovipositing females were observed when reared under non-diapause conditions and even in the non-diapause strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Murai et al (2001) reported that 28.6% of O. sauteri reared at 25°C using E. kuehniella eggs as the diet under long-day conditions (16L : 8D) did not lay eggs. Furthermore, Shimizu and Kawasaki (2001) reported the presence of non-ovipositing females even in the non-diapausing Okinawa strain of O. strigicollis reared as a colony at 20°C using E. kuehniella eggs as the diet under long-day conditions (16L : 8D). As shown in these results, nonovipositing females were observed when reared under non-diapause conditions and even in the non-diapause strain.…”
Section: Discussionmentioning
confidence: 99%
“…Although O. minutus is also a dominant species on eggplants (Ohno and Takemoto, 1997), some field data suggest that this insect may prefer trees as its host (T. Noda, unpublished data). On the other hand, O. strigicollis has been proposed as an effective biological control agent during the short days in the winter season because this species has a weaker reproductive diapause than O. sauteri, O. minutus, and O. nagai (Shimizu and Kawasaki, 2001;Kakimoto et al, 2003). O. strigicollis, O. sauteri, and O. minutus are frequently found together on various kinds of crops and herbaceous plants (Yasunaga, 1997b), and on deciduous trees such as mulberry, Morus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1993; Bush et al, 1993;Chyzik et al, 1995;Wearing andColhoun, 1999 1993 Orius sauteri Poppius 1989Dixon, 1959, 1994Kawai, 1995Kawai, 19881991 Shimizu andKawasaki, 2001 Nakashima et al,…”
mentioning
confidence: 99%
“…The northern Changchun population produced a higher incidence of diapause and had a higher critical temperature for diapause induction in most of the tested combinations than the southern Hangzhou population. Such variability in diapause trait between populations for most widespread insect and mite species has been well documented (Maslennikova and Mustafayeva, 1971;Weseloh, 1982;Brodeur and McNeil, 1989;Kraaijeveld and Alphen, 1995;McWatters and Saunders, 1996;Yoshio and Ishii, 1998;Ito and Nakata, 2000;Shimizu and Kawasaki, 2001;Kurota and Shimada, 2003;Gillespie and Quiring, 2005;Kato, 2005;Schmidt et al, 2005;Takafuji et al, 2005). The differences reflect physiological and ecological adaptations to local climatic conditions.…”
Section: Discussionmentioning
confidence: 85%